Pengaruh Wacc Terhadap Nilai Perusahaan (Studi Kasus pada PT Hanjaya Mandala Sampoerna Tbk dan PT Gudang Garam Tbk) - Supriadi, Yoyon (Sekolah Tinggi Ilmu Ekonomi Kesatuan, 2010)
The purpose of the research is to find out how much the capital structure influences the WACC (Weighted Average Cost of Capital ) and how much the WACC influences the company value at PT Hanjaya Mandala and PT Gudang Garam, Tbk. The analysis method applied is correlation coefficient to find out the relationship between the variables and the determination coefficient measuring the closeness of the relationship between the variables and the regression coefficient. This will then be applied to measure the influence of the free variables towards related variables as well as ration analysis to find out the proportion of each variables. The results of the research show that the proportion of the capital structure has significant influence towards WACC with t-count is 3591 bigger than t table with the score 2776 as well as the influence of WACCtowrds the value of shares with the score of t-count is 3624 and t table is 2776. At PT Gudang Garam, tbk the proportion of the capital structure also has significant influence towards WACC with the score of t-count is 3917 bigger than t table (2776) and influence of WACC towards the value of shares also significant. Key words: Weighted Average Cost of Capital, Company Value